Current Information Web applications using the programming language PHP Triad and Macromedia Dreamweaver. - Tino Qomariyadi (Jurnal Manajemen Informatika, 2010)
Making a web application is the latest information using research methods literature. The goal is tomake it easier for people to get the most recent information. This application is very useful especially anage now where people that need the ease and speed in obtaining the latest information.References (3.2004)